Victoria Ocampo and UNESCO – a visionary’s dream - United Nations Educational, Scientific; Cultural Organization; Lucía Iglesias Kuntz (The UNESCO Courier, 2023)
There are many convergences between the writer’s thinking and the Organization’s mandate. The story of a close bond.